A patient-centered composite endpoint weighting technique for orthopaedic trauma research - Udogwu, Ugochukwu N. (BMC Med Res Methodol, 2019)
BACKGROUND: This study aimed to address the current limitations of the use of composite endpoints in orthopaedic trauma research by quantifying the relative importance of clinical outcomes common to orthopaedic trauma patients and use those values to develop a patient-centered composite endpoint weighting technique. METHODS: A Best-Worst Scaling choice experiment was administered to 396 adult surgically-treated fracture patients. Respondents were presented with ten choice sets, each consisting of three out of ten plausible clinical outcomes. Hierarchical Bayesian modeling was used to determine the utilities associated with the outcomes. RESULTS: Death was the outcome of greatest importance (mean utility = − 8.91), followed by above knee amputation (− 7.66), below knee amputation (− 6.97), severe pain (− 5.90), deep surgical site infection (SSI) (− 5.69), bone healing complications (− 5.20), and moderate pain (− 4.59). Mild pain (− 3.30) and superficial SSI (− 3.29), on the other hand, were the outcomes of least importance to respondents. CONCLUSION: This study revealed that patients’ relative importance towards clinical outcomes followed a logical gradient, with distinct and quantifiable preferences for each possible component outcome. These findings were incorporated into a novel composite endpoint weighting technique.